Review: Flavonoid pada Tanaman Kumis Kucing (Orthosiphon stamineus Benth.): Review: Flavonoid Compounds in Orthosiphon stamineus - Fahrauk Faramayuda; Silvy Julian; Ari Sr Windyaswari; Totik Sri Mariani; Elfahmi Elfahmi; Sukrasno Sukrasno (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Orthosiphon stamineus has long been used in traditional medicine in East India, Indo China, Southeast Asia, and tropical Australia, where this plant is usually found. Based on the color of the flowers and petals, Orthosiphon stamineus is classified into two varieties: white flowers (white varieties) and purple flowers (purple varieties). Orthosiphon stamineus has traditionally been used to treat hypertension, diabetes, bladder and kidney disorders, gallstones, gout, and rheumatism. The leaves of Orthosiphon stamineus were introduced to Europe and Japan as tea for health. The main compounds possessed by Orthosiphon stamineus are rosmarinic acid, eupatorium, and sinensetin. In addition, several studies have isolated the plant of Orthosiphon stamineus. This journal review aims to review studies related to the content of secondary metabolites, traditional uses, pharmacological activities, and levels of flavonoids contained in plants.